Reducible burden of laryngeal cancer in men aged 50 and older attributable to smoking and alcohol use: insights from the global burden of disease study 2021 - Ru Chen; Jing Deng; Yao Sun; Dongxun Sun; Haibin Lu; Guoqi Sima (Frontiers in Public Health)
BackgroundSmoking, alcohol use, advanced age, and male gender are well-established risk factors for laryngeal cancer. As smoking and alcohol consumption are modifiable behaviors, the burden of laryngeal cancer attributable to these factors is potentially reducible. This study aims to quantify the global, regional and national burden of laryngeal cancer attributable to smoking and alcohol use in men aged 50 years and older, assess temporal trends from 1990 to 2021, and project the disease burden through 2040.MethodsThe burden of laryngeal cancer was assessed using data from the Global Burden of Disease 2021, including deaths, disability-adjusted life years (DALYs), years of life lost (YLLs), and years lived with disability (YLDs). The estimated average percentage change (EAPC) was used to evaluate trends in the disease burden from 1990 to 2021. Finally, projections for 2040 were generated and calculated with Nordpred.ResultsFrom 1990 to 2021, globally, the absolute burden of laryngeal cancer—measured by deaths, DALYs, YLLs, and YLDs—attributable to smoking and alcohol use increased among men aged 50 years and older, despite declining age-standardized rates (ASRs). Regionally, Central and Eastern Europe experienced the highest burden, which may be attributed to historically elevated rates of smoking and alcohol consumption in these regions. Countries with the greatest disease burden related to smoking at the national level include Cuba, Montenegro, Seychelles, Georgia, and Monaco, while Montenegro, Bulgaria, Romania, and Monaco have the highest alcohol-related burden. By 2040, the overall burden is projected to rise.ConclusionSmoking and alcohol-related laryngeal cancer will pose a significant public health challenge in the future. As the aging demographic continues to grow, the disease burden among older adult men is expected to rise. There are notable regional and national differences in terms of deaths, DALYs, YLLs, and YLDs. To address the rising burden, targeted public health actions are urgently required. These include higher taxation on tobacco and alcohol, comprehensive bans on related advertising, stricter enforcement of sales and age restrictions, enhanced health education regarding their health risks, and strengthened efforts in early screening.